Zsidó lojalitáshierarchiák változásai a lojalitás mint fogalom és mint értelmezési keret az újabb társadalomtudományos kutatásokban - Fenyves Katalin (Szegedi vallási néprajzi könyvtár, 2024)
The introductory study of this volume provides an overview of the evolving understanding of loyalty as both a concept and an interpretive framework in contemporary social science research. It offers a preliminary scholarly assessment by examining recent developments in the study of loyalty. The study delves into the growing scholarly interest in the analytical category of loyalty and discusses seminal works that have shaped the research agendas of the volume's contributors. In assessing the heuristic value of loyalty, the study explores potential new directions and theoretical approaches that could reinvigorate research focused on the application of loyalty categories. Additionally, the introduction briefly outlines the studies featured in this volume, highlighting their contributions within the framework of the loyalty concept.